Bilateral Trade, Openness and Asset Holdings - Alexandra Peter (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
This paper analyzes the relationship between bilateral trade flows, trade openness, and asset holdings in a three-country stochastic general equilibrium model. The threecountry model set-up enables me to disentangle and separate the effects bilateral trade flows and trade openness have on bilateral portfolio patterns. I find that both factors independently influence bilateral asset holdings. Higher bilateral trade as well as higher trade openness lead to a higher bilateral foreign asset position. Furthermore, the two factors show an interaction effect, where increasing trade openness diminishes the influence of bilateral trade flows on asset holdings. I provide supporting empirical evidence for these theoretical findings using a data set on the geographical composition of international portfolio holdings.
Keywords: F10; F30; F41; 330; International Portfolio Holdings; Bilateral Trade Flows; Trade Openness; Internationale Wirtschaftsbeziehungen; Politik der offenen Tür; Auslandsvermögen; Portfolio-Management; International; Theorie